Práticas e ambiências de leitura : reflexões a partir de escola de educação infantil em Nova Prata - Marchesini, Patricia (My University, 2022)
In order to children experience reading at a very young age, those responsible for school education need to be aware that reading is of paramount importance for the individual, both socially and individually. Although a small child is not yet inserted in the literate world, the interventions that they have through reading are a right of access to the symbolic world. In addition, it is a way of understanding the world, including oneself and the other. It is understood that literary reading contributes to the formation of the subject from early childhood and this principle supports this investigation, affiliated with the line of research Educational Processes, Language, Technology, and Inclusion. Under this conception, this research aims to investigate educational processes associated with reading, considering Early Childhood Education " daycare stage" in the municipality of Nova Prata/RS. The specific objectives are: a) to identify guidelines on reading for babies and very young children, taking as reference the National Common Curricular Base, the Gaucho Curriculum Reference and the PPP of the school taken as a study; b) to analyze, based on the interaction with professionals who work at this level of education, the reading practices developed in a kindergarten school in the municipality of Nova Prata, and c) to propose indicators for the construction of a baby library (bebeteca) for the investigated institution. The investigation intends to answer the problem question: based on the legal documentation of Early Childhood Education and on the voice of teachers in the municipality of Nova Prata, how are reading environments/actions for young children organized? Methodologically, this is a qualitative research carried out through a case study. The construction of the empirical study took place in an Early Childhood Education school through a focus group and individual interviews with teachers and daycare attendants who work with children from 0 to 3 years and 11 months old. As a result of the investigation, there was a lack of recognition of literary reading in the documents consulted. Also, that the professionals of the institution in question make use of different resources for the reading sessions, in addition to the physical book. They report that the sessions for the little ones at the daycare take place in the activities room and emphasize that the insertion of reading with babies is challenging. Simultaneously, even without an appropriate place for reading, it was possible to propose indicators for the creation of a baby library, configured according to the needs of the children in the daycare center and the wishes of the teachers and attendants. [resumo fornecido pelo autor]
Para as crianças experienciarem a leitura ainda bem pequenininhas, os responsáveis pela educação escolar precisam estar cientes de que a leitura é de suma importância para o indivíduo, tanto no âmbito social quanto individual. Apesar de uma criança pequena ainda não estar inserida no mundo letrado, as intervenções que ela tem mediante à leitura são um direito de acesso ao mundo simbólico. Além disso, é uma forma de compreensão de mundo, incluindo a si mesmo e ao outro. Entende-se que a leitura literária contribui para a formação do sujeito desde a mais tenra infância e tal princípio sustenta esta investigação, afiliada à linha de pesquisa Processos Educacionais, Linguagem, Tecnologia e Inclusão. Sob essa concepção, esta pesquisa tem como objetivo investigar processos educativos associados à leitura, tendo como cenário a Educação Infantil "etapa creche" no município de Nova Prata/RS. Os objetivos específicos são: a) identificar orientações acerca de leitura para bebês e crianças bem pequenas, tomando como referência a Base Nacional Comum Curricular, o Referencial Curricular Gaúcho e o PPP da escola tomada como estudo; b) analisar, a partir da interação com profissionais que atuam neste nível de ensino, as práticas de leitura desenvolvidas numa escola de Educação Infantil no município de Nova Prata, e c) propor indicadores para a construção de bebeteca para a instituição investigada. A investigação pretende responder à questão problema: com base na documentação legal da Educação Infantil e na voz de professoras do município de Nova Prata, como se organizam os ambientes/ações de leitura para crianças pequenas? Metodologicamente, trata-se de uma pesquisa qualitativa realizada por meio de estudo de caso. A construção da empiria ocorreu em uma escola de Educação Infantil por meio de grupo focal e de entrevistas individuais com professores e atendentes de creche que atuam com crianças de 0 a 3 anos e 11 meses de idade. Como resultado da investigação, constatou-se a falta de reconhecimento da leitura literária nos documentos consultados. Também, que, as profissionais da instituição em tela, fazem uso de diferentes recursos para as sessões de leitura, além do livro físico. Relatam que as sessões para os pequenos da creche acontecem na sala de atividades e ressaltam ser desafiador a inserção da leitura com bebês. Simultaneamente, mesmo sem um local apropriado para leitura, foi possível propor indicadores para criação de uma bebeteca, configurada de acordo com as necessidades das crianças da creche e dos anseios das professoras e atendentes. [resumo fornecido pelo autor]
Keywords: Leitura; Educação de crianças - Nova Prata (RS); Educação; Literatura; Reading; Education of children - Nova Prata (Brazil); Education; Literature